The Use of First Person Pronouns in Master’s Theses Written in English by Turkish Authors - Isler, Cemre ((JELE) Journal Of English Language and Education, 2018)
The purpose of this study is to investigate and compare the use of first person pronouns (I, my, me, we, our, us) and their functions in creating authorial self in 20 master’s theses written in English by Turkish authors and 20 research articles written in English by non-Turkish authors. Master’s theses used in the study were written in the field of English Language Teaching in twelve different Turkish universities and they were selected from the database of Turkish Council of Higher Education. Research articles used in the study were also written in the field of English Language Teaching and they were selected from five different journals: Applied Linguistics, System, TESOL Quarterly, English for Specific Purposes, and ELT Journal. For analyzing the data, each occurrence of first person pronouns in the theses and articles were coded and examined in order to find out the functions they serve. Results revealed a large difference in the use of first person pronouns and the functions they have. Turkish authors used these pronouns quite rarely and generally the use of these pronouns signaled low degree of authorial self; on the other hand, non-Turkish authors used these pronouns more frequently and they mostly preferred to use them for expressing greater degree of authorial self.